Effect of diaphragmatic breathing exercise on respiratory rate and oxygen saturation in patients with bronchial asthma - KK, Indra Frana Jaya (Science Center Group, 2024)
Background: Asthma is a chronic respiratory disorder characterized by airway narrowing and increased airway resistance, leading to recurrent episodes of dyspnea, wheezing, chest tightness, and coughing. Effective nursing management of asthma requires the identification and control of trigger factors as well as supportive interventions to improve respiratory function. One non-pharmacological intervention that can be applied in nursing care is the Diaphragmatic Breathing Exercise, which aims to enhance ventilation efficiency and oxygenation. Objective: This study aimed to analyze the effect of diaphragmatic breathing exercise on respiratory rate and oxygen saturation in patients with bronchial asthma. Methods: This study employed a quasi-experimental approach using a one-group pretest–posttest design. A total of 37 patients diagnosed with bronchial asthma were recruited using purposive sampling. Participants received the diaphragmatic breathing exercise intervention. Data were collected by measuring respiratory rate and oxygen saturation before and after the intervention. Statistical analysis was performed using the Wilcoxon signed-rank test to determine differences between pretest and posttest values. Results: The findings indicated a significant improvement in respiratory parameters after the intervention. The mean respiratory rate decreased from 24.95 (SD = 1.649) at pretest to 17.54 (SD = 1.789) at posttest, showing a statistically significant difference (p = 0.000). Oxygen saturation also demonstrated a significant change, with a mean pretest value of 96.16 (SD = 1.068) and a posttest value of 98.62 (SD = 0.681) (p = 0.000). These results suggest that diaphragmatic breathing exercise contributes to improved respiratory efficiency and oxygenation among patients with bronchial asthma. Conclusion: The implementation of diaphragmatic breathing exercise significantly reduces respiratory rate and improves oxygen saturation in patients with bronchial asthma. This intervention can be incorporated into nursing care as a simple, non-pharmacological strategy to enhance respiratory function and support holistic patient management. Nurses are encouraged to provide education and training on diaphragmatic breathing exercises as part of comprehensive asthma care.